An experimental study on the behavior of lime and silica fume treated coir geotextile reinforced expansive soil subgrade - Nitin Tiwari; Neelima Satyam (Engineering Science and Technology, an International Journal, 2020)
Structures constructed on expansive soils are experiencing higher upward pressure due to swelling- shrinkage nature of expansive soil. India has 15–20% expansive soil, which causes severe damage to the existing structure, including pavements, dams, multi-storey buildings, retaining walls. The aim of the study is to suitably reduce the distressed caused by the expansive soil on paved structures. The experimental result of expansive soil subgrade reinforced with and without coir geotextile mat has been presented in this paper. Lime and silica fume, treated and untreated coir geotextile mat with polypropylene fiber net has been used. A single and double layer of coir geotextile mat at various depths have been placed to evaluate the effect of reinforcement on expansive soil subgrade. The treatment was carried out to enhance the efficiency of coir geotextile for reducing the swelling pressure of the expansive soil subgrade. The chemical and microstructural components of expansive soil samples were investigated by using X-ray Diffraction (XRD) and Fourier Transform Infrared (FTIR). The constant volume swelling pressure, California Bearing Ratio (CBR) and large size direct shear (300 mm × 300 mm × 150 mm) tests have been carried out to evaluate the effect of treated and untreated coir geotextile on expansive soil subgrade. The experimental results analyzed indicates that the lime treated coir geotextile mat reduces the upward swelling pressure by 52.19% in single-layer and 81.89% in double-layer. The tangible improvement in the shear strength and bearing capacity of expansive soil subgrade was observed with the inclusion of lime treat coir geotextile. A lime treated coir geotextile in a single or double-layer can be used to stabilize the expansive soil subgrade. The improved property of reinforced expansive soil subgrade can reduce the thickness of the subbase and base course layer in paved structure.